Stilistika Populer Al-Quran dan Implikasinya Terhadap Pembelajaran Bahasa Arab - Moh. Buny Andaru Bahy; Khusnul Khitom; Ainur Ridho (Shaut al Arabiyyah, 2025)
Arabic as the language of the Quran is considered not a coincidence. Arabic was chosen by Allah because it has privileges among other languages in the world. One of them can be viewed in terms of the beauty of the language style or stylistics. Arabic language learning has gained the attention of language learning experts by conducting various studies and research to determine the effectiveness and success of various learning methods. The purpose of this study reveals how stylistics is popular in the Quran and its implications for learning Arabic using a qualitative descriptive approach. This research uses the library research method. The data is collected through documents, and comes from verses of the Quran contained in Yasin’s letter. While the analysis uses descriptive qualitative, both deductively and inductively. The results of the study found the fact that 15 metaphorical majas verses, 5 personification majas verses and 3 hyperbolic majas verses were found in Yasin’s letter which can be used as a reference for the concept of learning Arabic with its various advantages. Language elements that are seen as difficult for students can be presented separately, systematically according to the learning theme discussed.